Uma sequência de ensino sobre as leis de Newton: ampliando discussões para além da sala de aula - Martins, Flávio Antônio (2017)
The objective of this work was to elaborate and implement a Didactic Sequence in the teaching of physics in the High School, in order to enable the engagement of the students in the activities proposed by the teacher in the classroom. Using as teaching resources that value the dialogue and the participation of the students, which were mediated through methodologies such as: Peer Instruction (PI) and Just-in-Time Teaching (JiTT). With the elaboration of the Didactic Sequence from these methodologies, we believe we can contribute to broaden students' participation in Physics classes and also improve the communication between teacher-student and student-student outside the classroom, providing relevant discussions to generate an environment Motivator to teach and learn physics. And for this function was made a survey about the media most used by students and chose the WhatsApp, in which a group was created entitled "Physics of Uncle Flávio". In this group, the "space" of the classroom was extended, where the duly enrolled students held discussions and previous activities that enabled the teacher to structure their classes to meet the difficulties of these students. With the application of the sequence, students engage in activities and, mainly, in the discussions, in a gradual way, indicating that the discussions held in the classroom stimulated the participation in the discussions outside the classroom, in the WhatsApp group.